Analysis of etiology of loss of skin in lower limb and its reconstructive options - Devare, Abhishek; Bhatnagar, Arun (International Surgery Journal, 2020)
Background: The goal of lower extremity reconstruction in cases of skin loss is the coverage of defects and open wounds of the leg, so that they resume their life and prevent the deformity or amputation. Skin loss is either managed by dressings or surgically providing skin cover in the form of skin graft or flap. Methods: This was a prospective, observational hospital based study which involved 100 patients who were admitted in the ward with a diagnosis of skin loss in lower limb in Department of General Surgery and Department of Plastic surgery, Gandhi medical college and associated Hamidia Hospital, Bhopal, Madhya Pradesh from October 2017 to July 2019. Based upon history, clinical and local examination of the wound, necessary investigations, the plan of management, reconstructive procedure was done. The results were compared after one follow up. Results: The patients suffering were commonly males between 18-29 years and mostly due to trauma. Initial management of wounds with skin loss in lower limb was debridement and dressings. Commonly involved anatomical area was below knee area upto both malleoli. Reconstructive measures were commonly undertaken between 3-7 days. The commonest reconstructive option was split skin grafting. Commonly flap used was perforator based flap and local transposition flap. Conclusions: It can be concluded that the most common etiology responsible for the loss of skin in lower limb is trauma and the most used reconstructive measure in skin loss of lower limb is split skin grafting. Flap coverage acts as the best modality of reconstruction.